KUALITAS SEMEN BEKU SAPI BRAHMAN DENGAN DOSIS KRIOPROTEKTAN GLISEROL YANG BERBEDA DALAM BAHAN PENGENCER TRIS SITRAT KUNING TELUR - Nano Setiono; Sri Suharyati; Purnama Edy Santosa (JURNAL ILMIAH PETERNAKAN TERPADU, 2015)
The research was conducted at the Technical Service Unit Area - Regional Artificial Insemenation Center of Lampung, Terbanggi Besar District, Central Lampung Regency, Lampung Province on July 25th to 30th 2014, aims to: 1) determine the effect of different glycerol doses in yolk tris-sitrat diluent on Brahman’s frozen semen quality; 2) determine the best glycerol dose which can improve the Brahman bull’s frozen semen quality. The design used a completely randomized design with 5 treatments with glycerol doses in the yolk tris-sitrat diluent (5%, 6%, 7%, 8%, 9%) and 3 repetitions. The measured parameters were the percentage of sperm motility and live spermatozoa. The data were analyzed by analysis of variance with the real level 5% or 1% and continued with Orthogonal Polynomials test at significance level 5% or 1%. The results showed the different glycerol doses did not significantly effect (P>0.01) against the percentage of sperm motility and live spermatozoa post equilibration, but provides a significant influence (P<0.01)  against  the  percentage of  sperm  motility and  live  spermatozoa post  thawing.  Orthogonal polynomials test also showed the different doses of glycerol gives a significant influence (P<0.01) against the percentage of sperm motility and live spermatozoa post-thawing. The Effect of different glycerol doses  (5%, 6%, 7%, 8%, 9%) of the percentage sperm motility are 35.00%, 37.32%, 32.54%, 20.66%, 1.68% and the percentage of live spermatozoa post-thawing are 44.37%, 55.52%, 50.32%, 38.07%, 9.84%. Based on research results, it proved that 6% glycerol dose is the best dose to maintain the percentage of motility and live spermatozoa post-thawing.